PENGEMBANGAN LKS UNTUK METODE PENEMUAN TERBIMBING PADA PEMBELAJARAN MATEMATIKA KELAS VIII DI SMP NEGERI 18 PALEMBANG - Farida Aryani; Cecil Hiltrimartin (Jurnal Pendidikan Matematika, 2011)
The aim of this research are : (1) Producing the student worksheet for valid and practical guidance find method in math learning in the eighth class student in SMP Negeri 18 Palembang. (2) To know potential effect of the using student worksheet for guidance finder method to ability the eight class in SMP Negeri 18 Palembang. The research is developed learning practice plan, the student worksheet and the ability student test.This research use the development research method, and it contains analysis, design, evaluation and revision. The collecting data were used by observation and test. Observation use to analysis student activity along teaching learning process and the test use to analysis student ability. Subjects in this research are 40 students in the eight class in SMP Negeri 18 Palembang.The conclusion are: (1). the student worksheet are developed in this research is valid, practical and have potency effect for the student ability in the eighth class student in SMP Negeri 18 Palembang. (2). Prototype of the student worksheet is valid and practical. Valid were shown by validation evaluation that all validation result good base on content and construct and language. Practical were shown by every student can using the student worksheet good. (3) the student worksheet have potency effect to student ability. It were shown b the ability test result in good student ability level. Key words: guidance find method, student worksheet.